Antibiotic Use Is Not a Risk Factor of Infection by Extended-Spectrum Beta-Lactamase Producing Bacteria in Dr. Soetomo Hospital Surabaya (Microbiology Indonesia, 2015)
Infection by Extended-Spectrum Beta-Lactamase (ESBL) producing bacteria confers a major challenge for clinicians due to limited treatment options and poor prognosis. Inappropriate antibiotic use is thought to cause the emergence of this resistant strain through selective pressure mechanisms. This study aims to describe the proportion of ESBL-producing bacteria and characteristics of patients with ESBL-producing bacterial infection, and to analyze the risk factors of infection by ESBL-producing bacteria in Dr. Soetomo Hospital, Surabaya. A cross-sectional study was conducted on medical records of inpatients of Internal Medicine Ward of Dr. Soetomo Hospital. Samples were classified into ESBL-positive or ESBL-negative groups. Demographic data, clinical data and previous antibiotic use of 66 samples (33 in each group) were retrospectively obtained. As many as 30 patients (45.5%) were male. Mean age of patients in the ESBL-positive and negative group were 53.57 (Â±16.77) and 54.27 (Â±14.88) years, respectively (p>0.05). The median pre-infection length of stay was 4 and 3 days for ESBL-positive and negative group, respectively (p>0.05). Type 2 diabetes mellitus was the most common comorbid disease (33.3%). The most frequent bacteria obtained from clinical isolates was Escherichia coli (49.3%). Proportion of ESBL producers amongst E.coli and K. pneumoniae isolates were 75% and 38.5%, respectively. The most frequently prescribed empirical antibiotic was ceftriaxone. None of the antibiotic used were risk factors for infection by ESBL-producing bacteria. Although none of the assessed variables were risk factors for ESBL-infection was discovered, this study finds a significantly larger proportion of ESBL-E. coli compared to non-ESBL producing E. coli. Further studies should include larger sample size and quantitatively measured antibiotic use.